Mating Leads to a Decline in the Diversity of Symbiotic Microbiomes and Promiscuity Increased Pathogen Abundance in a Moth - Zhang, Luo-Yan; Yu, Hong; Fu, Da-Ying; Xu, Jin; Yang, Song; Ye, Hui (Frontiers in Microbiology, 2022)
Mating may promote microbial diversity through sexual transmission while mating-induced immune responses may decrease it. Therefore, study of mating induced microbiomes changes under different mating systems is informative to unravel its biological relevance and evolutionary significance. Here, we studied the microbiomes in a community context within the abdomen of Spodoptera frugiperda females using 16S rDNA sequences by setting virgin females, and females mated once, twice or thrice with the same or different males. Alpha and beta diversity revealed that mating significantly affected the composition of microbiomes in S. frugiperda females, wherein virgin females have the highest diversity, followed by one-time mated females and females mated with multiple males, while females mated repeatedly with the same male showed the lowest diversity. The low diversity in females mated repeatedly with the same male may be due to lower sexual transmission as only mated with one mate and higher immune response from repeated matings. Functional prediction by FAPROTAX and literature searching found seventeen possible pathogens and twelve beneficial microbiomes. Multiple mating turned over the abundance of pathogens and beneficial microbes, e.g., Enterococcus and Lactobacillus spp. (beneficial) showed higher abundance in virgin females while Morganella and Serratia spp. (pathogens) showed higher abundance in females mated with multiple males. These results suggest that mating causes a decline in the diversity of symbiotic microbiomes and promiscuity incurs a higher pathogen abundance in S. frugiperda females, which may be the result of sexual transmission of bacterial strains and immune responses targeting members of the microbiomes. To our knowledge, we demonstrate microbiomes changes in female insects under virgin and different mating regimes for the first time.